GAYA KOMUNIKASI FEMINIM DAN MASKULIN DI FILM MARS MET VENUS - Nurkhalisa, Waliya; Hasmawati, Fifi; Hamandia, Muhammad Randicha (Virtu: Jurnal Kajian Komunikasi, Budaya dan Islam, 2023)
ABSTRACT“Feminine and Masculine Communication Styles in the 2017 Mars Met Venus Film”. The interesting thing that made the researchers conduct this research was about feminine and masculine communication when in a romantic relationship, and the film Mars Met Venus 2017 raised how the differences in communication between women and men. The 2017 Mars Met Venus film divides the film into two parts, namely